Hubungan Self-Control dan Celebrity Worship pada Generasi Z Penggemar K-POP - Tengku Nazwa Utami; Satriati Pandita; Amanda Benita Putri; Untung Subroto (YASIN, 2026)
The development of Korean Pop (K-Pop) through social media and fan communities has encouraged Generation Z to engage in various fan club activities. Although such involvement can provide entertainment, social support, and a space for identity formation, excessive idolization may develop into celebrity worship; therefore, self-control is necessary to ensure that fan engagement remains adaptive. This study aimed to examine the relationship between self-control and celebrity worship among Generation Z K-Pop fans. The study employed a nonexperimental quantitative approach with a correlational design and involved 163 participants selected through purposive sampling. Data were collected using the 10-item Brief Self-Control Scale, with a reliability coefficient of α = 0.749, and the 25-item Celebrity Attitude Scale, with a reliability coefficient of α = 0.896. The data were analyzed using Pearson correlation after the assumption of normality had been met. The results showed a positive and significant relationship between self-control and celebrity worship (r = 0.522; p < 0.001). These findings indicate that high self-control does not necessarily reduce fans’ involvement with their idols but instead supports the more planned, proportionate, and healthy management of fan club activities, including the regulation of time, expenditure, and emotional responses. Conversely, limited self-control may lead to more impulsive and less structured fan activities. This study confirms that celebrity worship is a multidimensional phenomenon that is not necessarily maladaptive when balanced by strong self-control. These findings contribute to the development of social psychology research on fan behavior and provide practical implications regarding the importance of strengthening self-control among Generation Z so that their involvement in fan activities continues to provide psychological and social benefits without disrupting daily functioning.